Single Phase Transformer Less Inverter for Grid Connected Photo Voltaic System (International Journal of Scientific Research in Science and Technology, 2024)
Sustainable power generation systems have been developed as a result of increased consumption of energy, the rapid depletion of fossil fuels, and environmental degradation worldwide. Thus, the demand for photovoltaic systems is increasing, owing to the increased need for renewable resources worldwide. Transformers are often used in photovoltaic systems to offer voltage ratio conversions between input and output along with galvanic isolation. The inverter, that may be a transformer-less or with a transformer, is the enabling technology in PV systems. But, the efficiency and power density of these traditional iron and copper-based transformers are decreased while the inverter’s weight, size, and cost are increased. Thus, it is recommended to refrain from utilizing transformers within the inverter. For this reason, transformer-less inverters for grid-tied, low-voltage, single-phase photovoltaic (PV) systems have gained more attention thesedays. To comply with the safety requirements imposed by grid regulations, there are a few distinctive challenges, particularly with respect to leakage current problems, which need to be sufficiently handled. Owing to this In recent years, distributed solar grid-tied systems have made widespread use of single phase transformerless Voltage Source Inverters. This paper explores a novel transformer-less solar inverter for grid connected PV system and Results are investigated in MATLAB Simulink provided a significant reduction in distortion in voltage and current at load side.